PENGARUH PROGRAM FUL-TING (MINDFULNESS DAN EDUKASI STUNTING) TERHADAP PERILAKU IBU HAMIL DALAM PENCEGAHAN RISIKO KELAHIRAN DENGAN STUNTING - Handayani, Prita Adisty; Kristiyawati, Sri Puguh; Ryandini, Felicia Risca (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Background: Stunting is a condition of failure to thrive in children which can be seen from the child's length or height being less than his age. The risk of stunting can be determined from the beginning of pregnancy. Mothers who do not regularly attend pregnancy checks, do not consume balanced nutrition during pregnancy, and unclean environmental sanitation can cause suboptimal fetal development during pregnancy. The importance of pregnant women's understanding regarding these matters needs to be increased through several programs such as education and medical therapy as carried out in this research, namely through the FUL-Ting Program (Mindfulness and Stunting Education). Purpose: The purpose of this research is to see the effect of the FUL-Ting program on the behavior of pregnant women in preventing the risk of births with stunting. Method: The design of this research is Quasy-Experimental with Pretest Posttest Design without a Control Group. The research was conducted in August – September 2023 with 84 pregnant women as respondents. The instrument in this research uses a questionnaire to prevent stunting in pregnant women which has been tested for validity and reliability. The test used uses the Wilcoxon test. As a result, based on the test results, a p-value of 0.000 was obtained, so it can be concluded that there is an influence of the FUL-Ting program on the behavior of pregnant women in preventing the risk of births with stunting. In conclusion, the FUL-Ting program which consists of mindfulness therapy and stunting education can increase pregnant women's knowledge about stunting prevention. Apart from that, pregnant women consciously become more motivated and accept their current situation. So that changes in behavior to a more positive direction can be implemented after respondents receive the FUL-Ting program.